Gamified English Language Learning in the ESP Context - Ningrum, Sulistya (International Journal of English Language and Pedagogy, 2023)
Gamification is the use of game elements in non-game contexts to improve learning and engagement Although it has been increasingly recognized as a promising approach for enhancing English language learning, only a few studies have been conducted to investigate its roles, benefits, and drawbacks in English for Specific Purposes (ESP) pedagogy. This study discusses the use of gamification in language learning in ESP. This study employed a qualitative research approach, involving a collection and analysis of non-numerical data gathered from peer-reviewed journal articles and books. A literature review was used in the current study to provide an overview of the latest state of the literature on gamified English language learning in the ESP context. The novelty of the current study is to provide a complete review of the use of gamification in the ESP field, including the target audience, examples of gamification platforms, the gamification elements, the challenges, the effectiveness, the benefits, and the drawbacks of gamified English language learning. The target audience of gamified English language learning includes professionals or students seeking to improve their language skills for specific purposes. Gamification has been shown to provide several benefits, including increased motivation, active learning, and improved language proficiency. However, there are some challenges to the implementation of gamification in ESP, including curriculum integration, design and development, technology infrastructure, and assessment and evaluation.